Editor Membuat Volume - Yth, Yuldarahman (Indonesian Journal of Engineering and Computer Science, 2015)
AbstrakÂ AbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakÂ AbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrak